1995
DOI: 10.1128/jvi.69.6.3752-3758.1995
|View full text |Cite
|
Sign up to set email alerts
|

A subpopulation of normal B cells latently infected with Epstein-Barr virus resembles Burkitt lymphoma cells in expressing EBNA-1 but not EBNA-2 or LMP1

Abstract: Using reverse transcription of whole cellular RNA and nested PCR, we have performed experiments mixing different proportions of Epstein-Barr virus (EBV)-carrying and EBV-negative cells. Based on the results, a method that detects viral transcripts for EBNA-1, EBNA-2, LMP1, and LMP2a from less than one positive cell among 10 5 negative cells was developed. With this method we have shown that the EBV DNA positive cells among small, high-density peripheral blood B-lymphocytes of normal healthy persons express EBN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
59
1
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(68 citation statements)
references
References 44 publications
7
59
1
1
Order By: Relevance
“…As a consequence, certain latent genes (EBNA-2, EBNA-3A, EBNA-3C, EBNA-LP and LMP-1) have been apportioned an essential role in B cell transformation (Cohen et al, 1989;Hammerschmidt and Sugden, 1989;Mannick et al, 1991;Kaye et al, 1993;Tomkinson et al, 1993). However, the patterns of viral latent gene expression in cell culture and in vivo are profoundly different (Qu and Rowe, 1992;Chen et al, 1995). Moreover, viral expression in tumours differs from in vitro-infected B cells.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, certain latent genes (EBNA-2, EBNA-3A, EBNA-3C, EBNA-LP and LMP-1) have been apportioned an essential role in B cell transformation (Cohen et al, 1989;Hammerschmidt and Sugden, 1989;Mannick et al, 1991;Kaye et al, 1993;Tomkinson et al, 1993). However, the patterns of viral latent gene expression in cell culture and in vivo are profoundly different (Qu and Rowe, 1992;Chen et al, 1995). Moreover, viral expression in tumours differs from in vitro-infected B cells.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the advent of RT-PCR methodology as a tool to analyze the expression of critical genes in minute amounts of cells has paved the way to investigate the infection strategy of Epstein-Barr virus in vivo in normal and neoplastic cells (Klein, 1994). Thus far, a few studies have addressed this question by examining the pattern of EBV-gene expression in infected cells on peripheralblood mononuclear cells of healthy individuals (Qu and Rowe, 1992;Tierney et al, 1995;Chen et al, 1995). All the above studies have concluded that long-term persistence of EBV infection in vivo appears associated with the expression of a very limited number of EBV genes, namely EBNA-1 and/or LMP-2A.…”
Section: Detection Of Ebv-gene Transcription In Peripheral-blood Monomentioning
confidence: 99%
“…It is likely that the lower sensitivity of the RT-PCR strategy employed for the detection of EBNA-1 expression has led to under-estimation of the number of positive cases. Chen et al (1995) examined EBV-latent-gene-transcription status in small, high-density peripheral-blood B lymphocytes from normal healthy individuals. In that study, gene transcription encompassing either the Y3 or the Q exon was never detected.…”
Section: Detection Of Ebv-gene Transcription In Peripheral-blood Monomentioning
confidence: 99%
See 1 more Smart Citation
“…Tierney et al [2000a] reported that Wp was hypermethylated and that Cp was completely unmethylated in most patients with infectious mononucleosis. Promoter usage in healthy carriers is controversial [Tierney et al, 1994;Chen et al, 1995]. Paulson and Speck [1999] reported that Wp was hypermethylated but that Cp was only methylated sparsely to moderately in healthy carriers.…”
Section: Introductionmentioning
confidence: 99%